MM-GBSA and QM/MM simulation-based in silico approaches for the inhibition of Acinetobacter baumannii class D OXA-24 β-lactamase using antimicrobial peptides melittin and RP-1 - Manisha Mandal; Shyamapada Mandal (Chemical Physics Impact, 2024)
The antimicrobial peptides (AMPs) have been regarded as the next generation antibiotics. This study aimed to explore the AMP inhibitors of β-lactamase enzyme employing computational biology methods. Protein-peptide docking of Acinetobacter baumannii OXA-24 class D β-lactamase with AMPs (melittin and RP-1) were performed using HawkDock webserver. The docked complexes were subjected to energy property analysis through MM/GBSA, and binding affinity (ΔG (kcal/mol)) and stability (dissociation constant, KD (M)) prediction using PRODIGY. Both the AMPs, melittin and RP-1, were well docked with A. baumannii OXA-24. The top ranked OXA-24-melittin and OXA-24-RP-1 complexes were detected on the basis of the HawkDock scores (-2974.08 and -2825.83, respectively), thereafter by rescoring with MM/GBSA-based binding free energy (BFE) of -33.85 and -29.29 kcal/mol, respectively. The PRODIGY-based respective BFE (-8.0 and -10.0 kcal/mol) and KD (1.4 × 10-6 and 5 × 10-8 M) of the complexes revealed excellent protein-peptide binding affinity and complex stability. The iMODS-based molecular dynamic simulation authenticated the stability and molecular motion flexibility of the protein-peptide complexes. The quantum mechanics and molecular mechanics energy estimated using density-functional theory with CP2K software, for the electrostatic interaction of OXA-24-RP-1 (-218862.95 kcal/mol), was more favourable than the H-bonded interaction of OXA-24-melittin (-200620.21 kcal/mol), nevertheless both the peptides were found effective to inhibit OXA-24. Both the AMPs had toxicity profiles within the acceptable limits as predicted through pkCSM. Current findings indicate the potential supplement or replacement of conventionally used antibiotics with melittin and RP-1 to treating or averting A. baumannii infection by escaping the β-lactamases-mediated resistance.